The liver’s dilemma: sensing real danger in a sea of PAMPs: the (arterial) sinusoidal segment theory - Henriques-Pons, Andrea; Vacani-Martins, Natália; dos Santos, Carina de Lima Pereira; Meuser-Batista, Marcelo (Frontiers in Immunology, 2025)
The liver is susceptible to viruses and bacterial infections, tumors, and sterile tissue damage, but immunological danger recognition in the liver is highly unconventional. When analyzing innate and adaptive immunity in the organ, the valid concepts that guide danger recognition and immune response in the periphery should be put aside. In the liver, the vascular anatomy is a game changer, as about 80% of the blood that percolates the organ arrives from the hepatic portal vein, draining blood rich in molecules from the intestinal flora. This 24/7 exposure to high amounts of pathogen-associated molecular pattern (PAMPs) molecules results in hepatic immunological tolerance. In the liver, dendritic, Kupffer (KC), liver sinusoidal endothelial cells (LSECs), and even hepatocytes express PD-L1, a T lymphocyte downregulatory molecule. Most cells express Fas-L, IL-10, TGF-β, low levels of co-stimulatory molecules, lack of or have low levels of MHC-I and/or MHC-II expression. Moreover, other negative regulators such as CTLA-4, IDO-1, and prostaglandin E2 (PGE2) are regularly expressed. Then, how can real danger be discerned and recognized in this sea of PAMPs? This is an open question. Here, we hypothesize that conventional immunological danger recognition can occur in the liver but in specific and minor arterial sinusoidal segments,. Then, in the portal triad, where the hepatic artery ramificates into the stroma and carries arterial blood with no gut-derived PAMPs, there is no evolutive or environmental pressure for immunosuppressive pathways, and conventional immunological danger recognition could occur. Therefore, in arterial sinusoidal segments with no sea of PAMPs, the liver could recognize real danger and support innate and adaptive immunity.